Pendampingan Ekonomi Kreatif Melalui Limbah Anorganik Menjadi Peralatan Rumah Tangga - Suhono Suhono; Yayuk Hidayah; Muhyidin Thohir; Riyan Erwin Hidayat; Meiwatizal Trihastuti; Regina Prayoga (Bulletin of Community Engagement, 2021)
The problem of garbage was classical problem that is always faced by residents, especially in the Metro Lampung City. Because of the quantity and level of danger, especially plastic waste which was composed of chemicals, was difficult to decompose. Hence, It was dangerous for the environment. Therefore, it was necessary to process waste to convert plastic into crafts that have aesthetic and selling value. This research used participation action research (PAR), through analysis survey and the implementation of counseling and training. The implementation of the results of the processing of waste from plastic packaging into handicrafts was being carried out to increase the creativity and skills of community, especially housewives, unemployed youth and children who drop out of school. Besides that, it can also minimize environmental pollution so that metro city residents can care more about environmental cleanliness. Through training and assistance in making creations for the use of waste originating from plastic packaging, residents will have more knowledge about business opportunities that can be created through creativity and skills so that the economic level of residents becomes higher. Keywords: Economy Creative, Inorganic Waste, Community Engagement